Analysis of power converter topologies for variable reluctance motor drives - Wang, Jijiu. (2008)
Variable Reluctance Motor, also known as Switched Reluctance Motor (SRM), is a promising candidate for a wide range of applications. Besides its extremely simple and rugged construction, its unipolar current requirements also allow for a great variety of power converter topologies with minimal number of power semiconductor switches. This thesis reviews the known topologies, and describes the application of FEM-based simulation technique for SRM drive system, the analysis and comparison of typical topologies, and the proposition of a new topology. Mathematical analysis, simulations of the entire drive system, as well as results of experimental implementation are included in the thesis.